Case for transoral decompression of craniovertebral junction and C1 and odontoid for fixed atlanto axial dislocation and basilar invagination - Bhagavatula, Indira Devi (Indian Journal of Neurosurgery, 2013)
Transoral decompression of the craniovertebral junction is an established and safe method. Lateral atlanto-axial joints may be distracted and then fused posteriorly in some cases. The decision should be individualized based on the imaging and clinical picture.
Keywords: Basilar invagination; fixed atlanto axial dislocation; transoral decompression